PENERAPAN PENDEKATAN PEMBELAJARAN AKTIF, KREATIF, EFEKTIF DANMENYENANGKAN (PAKEM) DAN KONTEKSTUAL DALAM MENGATASIKESULITAN BELAJAR SISWA PADA PEMBELAJARANPENDIDIKANKEWARGANEGARAAN DI SMA MUHAMMADIYAH 2BANJARMASIN - Ansari, Ayu (Jurnal Pendidikan Kewarganegaraan, 2014)
Ayu Ansari, 2013. PAKEM approach and application Contextual on anticipated difficulties Learning in the teaching Citizenship Education at the Senior High School Muhammadiyah 2 Banjarmasin. Bachelor Theses Education Study Program Pancasila and Citizenship. Majoring Education Social Science Lambung Mangkurat University FKIP. Guide (I) Zainul Akhyar, Dian Agus (II). Some of the problems that need to be considered in order to optimize the process of learning for example, how to find how to best to get across the various concepts that are being taught so that the students and considering more can be used for a long time the concept, how a teacher can communicate effectively with the students, how one of the students can open horizons thinking with a degree of intelligence that are different from each student problems difficulties student learning. is all in the implementation teaching and learning in schools, such as a sign PKn as knowledge that is abstract and verbal Civic Education, of course different with the science of applied science that is sure, the theory and in fact it is different. This is the place where the PAKEM strategy implementation contextual learning and the application is used. Thus, to develop learning approach through innovations PAKEM approach and application contextual learning will be done is expected to make it easier to understand and in improving childrens learning motivation so that they can improve learning. This Research qualitative research method to use this method can give a chance for researchers to learn more in-depth counseling on the phenomenon takes place. Samples taking in the course of research terms qualitative used with caution. Qualitative research In the samples taking was to gather information as possible not to do generalizations. Samples taking charge to the situation, the subject, informers and time. Technical data collection that used in this research is a technique the observation, an interview in-depth documentation and literature. The focus observation done to the three components that is the place or space, the perpetrators, and activities, instrument or is guidelines interview, a little book, camera as tool documentation. Research on the field that has been done about PAKEM approach and contextual on anticipated difficulties learning students in the schools Muhammadiyah Senior High School 2 Banjarmasin has often been implemented, the PAKEM is being implemented in the process of learning thus the activity to learn a lesson to draw, there is a students involvement in the process of learning, students will be directed to become more active and easy to understand lessons and contextual approach also are going well, and the teachers as a facilitator to be able to relate to what is being taught between matter with the situation real world. Based on the results of research, it can be concluded that the application PAKEM approach and contextual on anticipated difficulties learning in the teaching Citizenship Education at the Senior High School Muhammadiyah 2 Banjaramasin has been running but must be improved, to reduce overcome the challenges or in the field but PAKEM and relevant is being implemented in the process of learning.